Reflections on Teaching Music 17: Hip Hop - Chodos, Asher Tobin (Current Musicology, 2019)
In 2019, my last year of graduate school, I taught the department’s undergraduate history of Hip Hop. This essay reflects on some of the many issues this course raises.